Effect of Berberine on Cardiovascular Disease Risk Factors: A Mechanistic Randomized Controlled Trial. - Zhao JV; Yeung W-F; Chan Y-H; Vackova D; Leung JYY; Ip DKM; Zhao J; Ho W-K; Tse H-F; Schooling CM (MDPI (Basel, Switzerland), 2021)
Cardiovascular disease (CVD) is a major contributor to the global burden of disease. Berberine, a long-standing, widely used, traditional Chinese medicine, is thought to have beneficial effects on CVD risk factors and in women with polycystic ovary syndrome. The mechanisms and effects, specifically in men, possibly via testosterone, have not been examined previously. To assess the effect of berberine on CVD risk factors and any potential pathway via testosterone in men, we conducted a randomized, double-blind, placebo-controlled, parallel trial in Hong Kong. In total, 84 eligible Chinese men with hyperlipidemia were randomized to berberine (500 mg orally, twice a day) or placebo for 12 weeks. CVD risk factors (lipids, thromboxane A2, blood pressure, body mass index and waist-hip ratio) and testosterone were assessed at baseline, and 8 and 12 weeks after intervention. We compared changes in CVD risk factors and testosterone after 12 weeks of intervention using analysis of variance, and after 8 and 12 weeks using generalized estimating equations (GEE). Of the 84 men randomized, 80 men completed the trial. Men randomized to berberine had larger reductions in total cholesterol (-0.39 mmol/L, 95% confidence interval (CI) -0.70 to -0.08) and high-density lipoprotein cholesterol (-0.07 mmol/L, 95% CI -0.13 to -0.01) after 12 weeks. Considering changes after 8 and 12 weeks together, berberine lowered total cholesterol and possibly low-density lipoprotein-cholesterol (LDL-c), and possibly increased testosterone. Changes in triglycerides, thromboxane A2, blood pressure, body mass index and waist-hip ratio after the intervention did not differ between the berberine and placebo groups. No serious adverse event was reported. Berberine is a promising treatment for lowering cholesterol. Berberine did not lower testosterone but instead may increase testosterone in men, suggesting sex-specific effects of berberine. Exploring other pathways and assessing sex differences would be worthwhile, with relevance to drug repositioning and healthcare.
Keywords: berberine; randomized controlled trial; testosterone; Adult; Anticholesteremic Agents; Berberine; Blood Pressure; Body Mass Index; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Double-Blind Method; Heart Disease Risk Factors; Humans; Hyperlipidemias; Male; Middle Aged; Testosterone; Thromboxane A2; Triglycerides; Waist-Hip Ratio